Frontispiece: Protein‐Templated Hit Identification through an Ugi Four‐Component Reaction. Issue 64 (18th November 2020) - Mancini, Federica; Unver, M. Yagiz; Elgaher, Walid A. M.; Jumde, Varsha R.; Alhayek, Alaa; Lukat, Peer; Herrmann, Jennifer; Witte, Martin D.; Köck, Matthias; Blankenfeldt, Wulf; Müller, Rolf; Hirsch, Anna K. H.
Abstract : The Ugi four‐component reaction (Ugi‐4CR) was employed as a new reaction in kinetic target‐guided synthesis (KTGS). Applying the reaction on the bacterial β sliding clamp (DnaN) (middle) resulted in marked acceleration of product assembly from a library of eight building blocks representing four chemical classes. UPLC‐HRMS analysis of the in situ Ugi‐4CR in the presence of the strong inhibitor griselimycin (left) or using endothiapepsin (right) as an unrelated protein revealed no product formation, demonstrating the specificity of the DnaN‐templated reaction. For more details see the Full paper by A. K. H. Hirsch et al. on page 14585 ff.